Analysis of Correlated MRC with Transmit Antenna Selection under eta-mu Fading - Téllez-Labao, Concepción; Pérez-Martín, Juan Pedro; Romero-Jerez, Juan Manuel (My University, 2017)
A wireless link considering correlated Maximal Ratio Combining (MRC) and Transmit Antenna Selection (TAS)under the general eta-mu fading is analyzed. Exact and asymptotic expressions for the cumulative distributing function (CDF) and probability density function (PDF) are derived. These new results are used to evaluate the outage capacity and the asymptotic average bit error rate (average BER) for different binary modulations. The obtained theoretical results are validated through MonteCarlo simulations.
Keywords: Comunicaciones; generalized fading; asymptotic analysis; bit error rate